The Interlanguage Verb Tenses Study: A Case Study on Rena Aprilia - Rahma Deni; Fahriany Fahriany (ELITE JOURNAL, 2020)
Among aspect of study on second language acquisition, Interlanguage is one of the most important one. The presents study explore the interlanguage verb tense that centers on investigating the interlanguage made by Rena Aprilia, a third-semester of communication science student of Syarif Hidayatullah State Islamic University of Jakarta. Qualitative research with case study design administrated in order to identify and collect the data on Rena’s composition on the interlanguage error specifically on using the simple present tense and simple past tense. The author collects the data through fourth-time semi-structure interview and document which derives from Rena's diary about her daily routine. The result revealed that Rena creates her language system when producing a target language. The new system is between her target language (English) and her native language (Bahasa Indonesia). There are four Interlanguage patterns made by Rena to indicate the same events which are simple present and three patterns to indicate past events.